Editorial - Sbarra, Alberto (1998)
El autor presenta el número de la revista dedicado a la temática de la vivienda.
Keywords: ARGENTINA; BUENOS AIRES (PROV); LA PLATA; PUBLICACIONES PERIODICAS; REVISTAS; FAU; UNLP; VIVIENDA